An exploratory study assessing compliance among municipal controllers and the possible explanations for their degree of compliance. Issue 3 (17th December 2019) - Anderson, Rick; Maks, Herbert; Klaassen, Henk
Abstract : Municipal controllers are sometimes confronted with requests from managers that contradict with the legal provisions. This raises the question how municipal controllers deal with these requests and whether this would impact their compliance. This article is a result of an exploratory study assessing compliance among municipal controllers and the possible explanations for their degree of compliance. The study has focused on one specific provision concerning accrual accounting, one of the elements of new public management (NPM), which is prescribed for Dutch municipalities. The study is based on a survey in 22 municipalities. The results show that the majority of municipal controllers who participate in this study deviate from this legal provision. There might be a relation between the orientation of the controllers and the degree of compliance. The position of the controller within the municipality can be a significant factor explaining this orientation. However, the size of the sample is too limited to generalize. The conclusions of this study undermine the idea that municipal controllers should act as business partners to the management. Finally, the study reveals a paradox: while one of the main elements of NPM is to shift more responsibilities to decentralized managers, this shift can lead to an increased principal‐agent problem, leading to a lesser degree of compliance.